1982
DOI: 10.1111/1523-1747.ep12507367
|View full text |Cite
|
Sign up to set email alerts
|

“Of Mice and Men” the Cell Cycle in Human Epidermis in Vivo

Abstract: This article deals with and compares cell cycle information obtained in mouse and in human epidermis in vivo. In order to compare data in mouse and in man, DNA labeling and mitotic index experiments were performed to obtain cell cycle information in normal human epidermis in vivo. Experiments were also performed on genetically inbred and outbred strains of mice--to provide a clue to the differences observed between mouse and man. The article makes the following points: 1. In contrast to mouse epidermis, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
2
11
1
Order By: Relevance
“…In our studies we found that intermediate and periderm cells, as well as basal cells, were labeled; and, therefore, we calculated labeling indices for each cell type (see Table 2). Our data, however, agree with previously published results (Stern, 1974) if basal and intermediate cell labeling indices (Potten, 1975;Gelfant, 1982) and that the needed increased rate of epidermal cell production appears to be provided by the intermediate cell layer. It is also interesting to note that the labeling index of adult skin in this organ culture system was approximately 5%, a figure well within the previously reported in uiuo labeling indices of adult skin (Potten, 1975), which suggests that, within the first day, this organ culture system does not measurably alter the proliferative rates of specimens.…”
Section: Discussionsupporting
confidence: 93%
“…In our studies we found that intermediate and periderm cells, as well as basal cells, were labeled; and, therefore, we calculated labeling indices for each cell type (see Table 2). Our data, however, agree with previously published results (Stern, 1974) if basal and intermediate cell labeling indices (Potten, 1975;Gelfant, 1982) and that the needed increased rate of epidermal cell production appears to be provided by the intermediate cell layer. It is also interesting to note that the labeling index of adult skin in this organ culture system was approximately 5%, a figure well within the previously reported in uiuo labeling indices of adult skin (Potten, 1975), which suggests that, within the first day, this organ culture system does not measurably alter the proliferative rates of specimens.…”
Section: Discussionsupporting
confidence: 93%
“…This kinetic profile is comparable to the in vivo antigen kinetics observed on DNA tattooing of mice (Bins et al, 2005). This rather transient nature of vaccine-induced antigen expression in skin may possibly be explained by the high turnover of the epidermis (Gelfant, 1982) but could also be due to gene silencing. Importantly, it has previously been shown that fresh skin in culture does not lose its viability in the first 30 hr of culturing, with a viability decrease of 50% after 60 hr in medium at 378C (Castagnoli et al, 2003;Messager et al, 2003).…”
Section: Van Den Berg Et Alsupporting
confidence: 76%
“…Since human skin is a renewable tissue that undergoes loss and replacement of all keratinocytes approximately every 21 days or less in the wound-like environment of a skin graft (17,20,48), successful skin gene therapy requires gene targeting to keratinocyte progenitor cells for persistent expression in a high percentage of keratinocytes. These studies represent the first comprehensive assessment of keratinocyte transduction by lentiviral vectors and also demonstrate the advantages of using grafts of human skin equivalents as an in vivo assay to assess the ex vivo transduction of keratinocyte progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our ex vivo model, the grafted human keratinocytes would be expected to completely turn over every 2 to 3 weeks, and all genetically engineered keratinocytes would be lost unless progenitor cells were stably transduced (17,19,20,48). Therefore, the ability of lentiviral vectors (or retroviral vectors) to introduce genes into keratinocyte progenitor cells can be determined by the percentage of human keratinocytes expressing GFP after several epidermal turnovers, analogous to biological models assessing hematopoietic stem cell targeting (7,13,34,(52)(53)(54).…”
Section: Lentiviral Vectors Are Superior To Retroviral Vectors In Tramentioning
confidence: 99%